Fasting inhibits aerobic glycolysis and proliferation in colorectal cancer via the Fdft1-mediated AKT/mTOR/HIF1α pathway suppression - Mei-lin Weng (Nature Portfolio, 2020)
The molecular mechanisms underpinning how fasting inhibits tumourigenesis are not completely elucidated. Here, the authors show that fasting upregulates the cholesterogenic gene FDFT1 which leads to decreased AKT/mTOR/HIF1a signalling and glycolysis reduction in colorectal cancer.